Plio-Pleistocene climatic change drives allopatric speciation and population divergence within the Scrophularia incisa complex (Scrophulariaceae) of desert and steppe subshrubs in Northwest China - Wang, Rui-Hong; Yang, Zhao-Ping; Zhang, Zhi-Cheng; Comes, Hans Peter; Qi, Zhe-Chen; Li, Pan; Fu, Cheng-Xin (Frontiers in Plant Science, 2022)
Numerous temperate plants and animals on the Qinghai-Tibet Plateau (QTP) are hypothesized to have differentiated due to vicariant allopatric speciation associated with the geologic uplifts. However, this hypothesis has rarely been tested through a phylogeographic study of relative species in a broader geographic context, including the QTP, Tianshan Mountains, Mongolian Plateau, and surrounding regions. To understand the speciation and diversification process of plants across this wide area, phylogeographic analysis were examined from Scrophularia incisa and two other closely relative species comprising S. kiriloviana and S. dentata. Thirty-two populations of the three close relatives were genotyped using chloroplast DNA fragments and nuclear microsatellite loci to assess population structure and diversity, supplemented by phylogenetic dating, ancestral area reconstructions and species distribution modelings, as well as niche identity tests. Our chloroplast DNA (cpDNA) phylogeny showed that this monophyletic group of desert and steppe semi-shrub is derived from a Middle Pliocene ancestor of the Central Asia. Lineages in Central Asia vs. China diverged through climate/tectonic-induced vicariance during Middle Pliocene. Genetic and ENM data in conjunction with niche differentiation analyses support that the divergence of S. incisa, S. dentata and S. kiriloviana in China lineage proceeded through allopatric speciation, might triggered by early Pleistocene climate change of increase of aridification and enlargement of deserts, while subsequent climate-induced cycles of range contractions/expansions enhanced the geographical isolation and habit fragmentation of these taxa. These findings highlight the importance of the Plio-Pleistocene climate change in shaping genetic diversity and driving speciation in temperate steppes and deserts of Northwestern China.